Direct effectiveness of adding local hyperthermia to the scheme of neoadjuvant chemoradiotherapy for locally advanced rectal cancer - S. A. Ivanov; L. O. Petrov; D. V. Erygin; I. A. Gulidov; A. A. Karpov (Исследования и практика в медицине)
Purpose of the study. Direct evaluation of the antitumor effectiveness of neoadjuvant chemoradiotherapy for rectal cancer using local electromagnetic hyperthermia. Materials and methods. The analysis of the direct results of treatment of patients with locally advanced rectal cancer in the clinic of the MRRC them. A.F.Tsyba is a branch of the Federal State Budgetary Institution Scientific Research Center for Radiology of the Ministry of Health of Russia from 2015 to 2018. The study included 2 groups of patients: the study group of 54 patients and the control group of 56 people. All patients underwent a comprehensive examination with the aim of staging and morphological verification of the tumor. Patients of the study group in the neoadjuvant mode received conventional radiation therapy with classical dose fractionation in ROD 2 Gy, up to SOD 50 Gy, for 5 weeks with CAPOX chemotherapy, and local electromagnetic hyperthermia on the Yacht 4 unit, in the amount of 6 sessions. Patients in the control group received neoadjuvant treatment in an absolutely identical manner, with the exception of local hyperthermia. After the end of neoadjuvant therapy after 8–10 weeks, a comprehensive examination was again performed to assess the response of the tumor and a decision was made to conduct surgical treatment. During the follow-up examination, the following parameters were evaluated: tumor regression according to clinical and radiological examination. After surgical treatment, a comprehensive evaluation of the removed drug was carried out, including an assessment of the degree of therapeutic tumor pathomorphism according to Lavnikova G. P. Results. When conducting a comparative analysis of the frequency of complete clinical regressions of the tumor in the thermo-chemoradiotherapy group, we more often recorded the full clinical response, 12 patients (22%), compared with the chemoradiotherapy group, 8 patients (14%). In terms of partial response and stabilization in the chemoradiotherapy group, partial regression was observed in 75% of patients, while in the thermochemioradiation group only in 52% of cases. Stabilization in the study and control groups was 14% and 6%, respectively. All patients of the study and control groups with partial tumor regression and stabilization underwent surgical treatment. As a result, the frequency of surgical operations in the control group was slightly higher than 48 (85.7%) versus 42 (77.7%) from the main group (p>0.05). When analyzing the frequency of a complete pathomorphological response, we noted that in the thermochemo-radiation therapy group it was 34% versus 4% in the chemo-radiation therapy group. On the contrary, pathomorphism of the 1st degree was much more common in patients of the control group — 21% versus 2% in the study group. The differences in both cases are statistically highly significant (p<0.001, χ2 15, χ27). Conclusion. The use of thermochemoradiotherapy with high statistical significance (p<0.001) increases the frequency of complete pathomorphological response: 34% in the study group versus 4% in the chemoradiotherapy group.